STUDY OF ZOONOTIC HELMINTHS OF CARNIVORES IN KHUZESTAN, IRAN - A. Farahnak; I. Mobedi; F. Mohamadi (Tehran University of Medical Sciences, 1998)
In this survey 45 carnivores including 14 Jackals, 23 stray dogs, 2 foxes, 2 domestic cats, 1 wild cat, 2 swine and 1 wolf were collected. On post-mortem examination, 84% carcases were infected and 13 zoonotic helminth species were recovered. Dirofilaria immitis was the most commonly parasite and Toxocara canis showed the highest intensity of infection. One species from swine and two helminth species from wolf were reported for the first time in Iran.